2014
DOI: 10.1111/jcmm.12407
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a proteome profile and identification of molecular markers for mouse spermatogonial stem cells

Abstract: Spermatogonial stem cells (SSCs) are undifferentiated cells that are required to maintain spermatogenesis throughout the reproductive life of mammals. Although SSC transplantation and culture provide a powerful tool to identify the mechanisms regulating SSC function, the precise signalling mechanisms governing SSC self-renewal and specific surface markers for purifying SSCs remain to be clearly determined. In the present study, we established a steady SSC culture according to the method described by Shinohara'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…On the next day, floating cells were transferred to another plate and then passaged 2 or 3 times before use. The SSC culture medium was prepared as described in Zhou et al (17).…”
Section: Isolation Of Sscsmentioning
confidence: 99%
“…On the next day, floating cells were transferred to another plate and then passaged 2 or 3 times before use. The SSC culture medium was prepared as described in Zhou et al (17).…”
Section: Isolation Of Sscsmentioning
confidence: 99%
“…Moreover, in our previous study, we showed that stromal interaction molecule 1 (STIM1) is required for testicular cord formation via gonad culture. Besides testicular culture, cultured SSCs are a proven stable platform for exploring SSC development 192526. For example, in our previous work, we established a steady SSC culture method and fertile progeny were produced after transplantation of cultured SSCs into infertile mouse testis.…”
Section: Discussionmentioning
confidence: 99%
“…For each experiment, at least eight explants were pooled from the testes of 3 mice in each group. For SSC culture, long-term culture of mouse SSCs was established in accordance with a previous described protocol 19. Briefly, dissociated testicular cells were cultured overnight on a 0.2% ( w/v ) gelatin-coated tissue culture plate (2 × 10 5 cells per 3.8 cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Since Sato et al first obtained functional sperm in cultured neonatal mouse testes (Sato et al 2011), this culture method has been widely used as a platform for the mechanistic understanding of spermatogenesis by several researchers (Chen et al 2014, Zheng et al 2014b. As for SSC culture, it is also a stable platform for exploring the development of spermatogonial stem cells and molecular mechanisms of spermatogenesis (Zhou et al 2015, Kanatsu-Shinohara et al 2016, Helsel et al 2017, Wang et al 2017. However, future studies investigating the detailed molecular mechanism of CNBP in testes using conditional knockout mouse models are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term culture of mouse SSCs was established in accordance with a previous described protocol (Zhou et al 2015). Briefly, testis from 2-day neonatal mice was digested with 1 mg/mL collagenase (type IV; Sigma-Aldrich) for 15 min, followed by 0.25% trypsin EDTA (Invitrogen) with 1.4 mg/mL DNase (Sigma-Aldrich) for 10 min.…”
Section: Ssc Culturementioning
confidence: 99%